Practice-Based Research as Reciprocal Protocol: Constellations of Care in The Seventh Fire - Cooke Ravensbergen, Lisa (Performance Matters)

(untitled) (Institute for Performance Studies, Simon Fraser University, 2023)
The Seventh Fire is an immersive audio performance that sources traditional, oral Anishinaabe stories and societal roles as a way to evoke ceremony in the everyday. I use the experience of creating this new form and premiering this work as an opportunity to reflect on principles of reciprocity that underscore and infuse any practice-based inquiry, as well as propose some necessary structures of care to support these principles.